Attentional Capacity during Dual-task Balance Performance Deteriorates with Age before the Sixties. Issue 1 (1st January 2022) - Bech, Signe R; Kjeldgaard-Man, Lotte; Sirbaugh, Monica C; Egholm, Anisette F; Mortensen, Svanna; Laessoe, Uffe
ABSTRACT: Postural control may be automated and leave residual attentional capacity for concurrent cognitive challenges – i.e. dual-task capacity. In old people and impaired individuals, the automatization is lost but dual-task performance may deteriorate even earlier in life. A convenience sample of 112 healthy individuals represented three subgroups: <30 years, 30–60 years and >60 years. They were challenged in a novel dual-task test on postural control and attentional capacity, which allowed participants to improve the performance time compared with their baseline provided they had residual attentional capacity to utilize leading cues in their movement strategies. Performance time in the baseline motor task (single task) increased with age, and relative improvement with cue (attentional capacity during dual task) decreased with age: correlation coefficients: 0.32 and −0.41. There were differences between the age groups in the improvement with cues: young 26.6% (6.6), middle aged 19.1% (12.2) and elderly 10.1% (11.6). In general, all age groups performed the task faster with cues, but individual differences were large. The middle-aged group as well as the elderly group had a poorer dual-task performance than the young group. This suggests that attentional capacity during dual-task balance may be affected even before the sixties.